2006
DOI: 10.1029/2006gl025962
|View full text |Cite
|
Sign up to set email alerts
|

Recent glacial recession in the Rwenzori Mountains of East Africa due to rising air temperature

Abstract: [1] Based on field surveys and analyses of optical spaceborne images (LandSat5, LandSat7), we report recent decline in the areal extent of glaciers in the Rwenzori Mountains of East Africa from 2.01 ± 0.56 km

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 24 publications
4
77
0
1
Order By: Relevance
“…This implies that the recent Kilimanjaro ice loss was due not to drying, but primarily to atmospheric warming. Taylor et al (2006) suggested that a warming trend has been the primary driver of glacier recession in the Rwenzori Mountains, matching the extent of recession to local meteorological records.…”
Section: Discussionmentioning
confidence: 77%
“…This implies that the recent Kilimanjaro ice loss was due not to drying, but primarily to atmospheric warming. Taylor et al (2006) suggested that a warming trend has been the primary driver of glacier recession in the Rwenzori Mountains, matching the extent of recession to local meteorological records.…”
Section: Discussionmentioning
confidence: 77%
“…The annual precipitation is estimated at about lwe 20 cm (Mörth, 1970;Hastenrath, 1984, p. 17;Hemp, 2005). For Rwenzori (Figure 1(b)) there is an ample evidence of drastic and progressive shrinkage of ice area (Hastenrath, 1984(Hastenrath, , 2005b(Hastenrath, , 2006Kaser and Osmaston, 2002;Taylor et al, 2006), but no quantitative information on changes in ice thickness. …”
Section: Observationsmentioning
confidence: 96%
“…A drastic and progressive shrinkage of ice extent is indeed indicated for the Ecuadorian Andes and New Guinea (Hastenrath, 1981(Hastenrath, , 2008Klein and Kincaid, 2006), and particularly well documented for the glaciated high mountains of East Africa (Hastenrath, 1984(Hastenrath, , 2005a(Hastenrath, , 2005b(Hastenrath, , 2006(Hastenrath, , 2008Hastenrath and Greischar, 1997;Kaser and Osmaston, 2002;Taylor et al, 2006), Mount Kenya, Kilimanjaro and Rwenzori (Figure 1(b)). The relation to climatic change appears qualitatively obvious.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Glacial water reservoirs on the peaks of Rwenzori and Mount Kenya are facing serious threats [33] [34], which are largely attributed to raising air temperatures and reduced humidity including rainfall. In the Lubombo, vegetation change over a period of 70 years has reduced grazing space for cattle.…”
Section: Effect Of Climate Changementioning
confidence: 99%